2018
DOI: 10.1128/aem.02491-17
|View full text |Cite
|
Sign up to set email alerts
|

The Babesia divergens Asia Lineage Is Maintained through Enzootic Cycles between Ixodes persulcatus and Sika Deer in Hokkaido, Japan

Abstract: Parasites of the Asia lineage, which are closely related to in Europe and sp. strain MO1 in the United States, were recently reported in sika deer () in eastern Japan. To identify the tick vector(s) for this parasite, we conducted a field survey in Hokkaido, Japan, where the infection rate in sika deer is the highest in the country. A specific PCR system which detects and discriminates between lineages within and between those lineages and showed that (11/822), but not sympatric (0/595) or sp. (0/163) ticks, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Human babesiosis has been reported in China, including cases of infection with B. microti (116) and B. venatorum (117), which is endemic in northwestern China. Although several studies have reported the incidence of B. divergens or B. microti in ticks and mammals in Japan (118)(119)(120)(121), to date, only sporadic human cases have been reported (122). Similarly, India (123), Egypt (124), the Democratic Republic of the Congo (125), and Australia (126) have occasionally reported human cases.…”
Section: Epidemiology and Ecologymentioning
confidence: 99%
“…Human babesiosis has been reported in China, including cases of infection with B. microti (116) and B. venatorum (117), which is endemic in northwestern China. Although several studies have reported the incidence of B. divergens or B. microti in ticks and mammals in Japan (118)(119)(120)(121), to date, only sporadic human cases have been reported (122). Similarly, India (123), Egypt (124), the Democratic Republic of the Congo (125), and Australia (126) have occasionally reported human cases.…”
Section: Epidemiology and Ecologymentioning
confidence: 99%
“…Notably, the presence of B . divergens outside Europe and North Africa was recently confirmed in China and Japan [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…Babesia divergens is primarily transmitted by the sheep or castor bean tick Ixodes ricinus, which is the dominant tick species throughout Europe, although the Asian lineage of B. divergens is probably transmitted by Ixodes persulcatus (4). Both species are three-host ticks and usually require 3-6 years to complete their life cycle (5).…”
Section: Introductionmentioning
confidence: 99%